Evaluating the environmental parameters that determine aerobic biodegradation half-lives of pesticides in soil with a multivariable approach. (October 2018) - Wang, Yuxin; Lai, Adelene; Latino, Diogo; Fenner, Kathrin; Helbling, Damian E.
Abstract: Aerobic biodegradation half-lives (half-lives) are key parameters used to evaluate pesticide persistence in soil. However, half-life estimates for individual pesticides often span several orders of magnitude, reflecting the impact that various environmental or experimental parameters have on half-lives in soil. In this work, we collected literature-reported half-lives for eleven pesticides along with associated metadata describing the environmental or experimental conditions under which they were derived. We then developed a multivariable framework to discover relationships between the half-lives and associated metadata. We first compared data for the herbicide atrazine collected from 95 laboratory and 65 field studies. We discovered that atrazine application history and soil texture were the parameters that have the largest influence on the observed half-lives in both types of studies. We then extended the analysis to include ten additional pesticides with data collected exclusively from laboratory studies. We found that, when data were available, pesticide application history and biomass concentrations were always positively associated with half-lives. The relevance of other parameters varied among the pesticides, but in some cases the variability could be explained by the physicochemical properties of the pesticides. For example, we found that the relative significance of the organic carbon content of soil for determining half-lives depends on the relative solubility of the pesticide. Altogether, our analyses highlight the reciprocal influence of both environmental parameters and intrinsic physicochemical properties for determining half-lives in soil. Highlights: Aerobic biodegradation half-lives collected from literature for eleven pesticides. Multivariable framework developed to link environmental metadata to half-lives. Application history and biomass always positively associated with half-lives. Relevance of other metadata depend on physicochemical properties of pesticide. Results provide quantitative link between half-lives and partitioning behavior.